Factors affecting environmental organisational citizenship behaviour / Luqman Mahmud, Ahmad Nizan Mat Noor and Shaiful Annuar Khalid - Mahmud, Luqman; Mat Noor, Ahmad Nizan; Khalid, Shaiful Annuar (Research Management Institute (RMI), 2023)
Organisational Citizenship Behaviours directed towards the environment or can be called as Environmental Organisational Citizenship Behaviour (OCBE) is an individual engaging in voluntary and unrewarded environmental actions that go beyond their requirements. In order to lead individual in ecologically friendly behaviour, there are few values that need to be tested. The researcher used only three factors which are environmental concern, perceived organisational support and affective commitment. This study was conducted among the employees at Ministry of Work to identify whether these values have any significant influence with the OCBE in impacting the organisation to comply with the new environmental regulation in reducing negative environmental impacts. This is to help the organization to address the needs that helps them to identify the possible factors that can influence the OCBE of the employees who works in their organisation. In this study, 200 questionnaires was distributed to the management sectors employee in the Ministry of Works. The researcher conducted reliability analysis, Pearson correlation analysis and multiple regression analysis in order to test the hypothesis. The finding results confirmed only one variable which was perceived organisational support that significantly influenced OCBE.